Highly Luminescent Inks: Aggregation‐Induced Emission of Copper–Iodine Hybrid Clusters - Chen, Chen; Li, Rui‐Han; Zhu, Bai‐Sheng; Wang, Kun‐Hua; Yao, Ji‐Song; Yin, Yi‐Chen; Yao, Ming‐Ming; Yao, Hong‐Bin; Yu, Shu‐Hong (Angewandte Chemie International Edition, 2018)
Aggregation‐induced emission (AIE) is an attractive phenomenon in which materials display strong luminescence in the aggregated solid states rather than in the conventional dissolved molecular states. However, highly luminescent inks based on AIE are hard to be obtained because of the difficulty in finely controlling the crystallinity of AIE materials at nanoscale. Herein, we report the preparation of highly luminescent inks via oil‐in‐water microemulsion induced aggregation of Cu–I hybrid clusters based on the highly soluble copper iodide‐tris(3‐methylphenyl)phosphine (Cu4I4(P‐(m‐Tol)3)4) hybrid. Furthermore, we can synthesize a series of AIE inks with different light‐emission colors to cover the whole visible spectrum range via a facile ligand exchange processes. The assemblies of Cu–I hybrid clusters with AIE characteristics will pave the way to fabricate low‐cost highly luminescent inks. Ink‐lined to glow: Highly luminescent inks based on AIE Cu–I hybrids clusters are prepared by the self‐assembly of Cu–I hybrid cluster aggregates in microemulsion droplets. A subsequent ligand exchange step expands the color pallet of the as‐fabricated inks.